2017
DOI: 10.3168/jds.2016-12074
|View full text |Cite
|
Sign up to set email alerts
|

Health, physiology, and behavior of dairy calves reared on 4 different substrates

Abstract: The objective of this study was to compare the health, physiology, and behavior of group-housed calves reared on wood shavings with those reared on alternative surfaces. At 1 wk of age, 80 calves were moved into 1 of 20 experimental pens (n = 4 calves/pen) where they remained until 6 wk of age. Pens had floors covered with pea gravel (PG), rubber chip (RC), sand (SA), or wood shavings (WS; n = 5 pens/substrate). Body weight, cleanliness, health, and skin surface and vaginal temperature were recorded at 1, 3, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
6
15
0
Order By: Relevance
“…In this study, skeletal growth at the end of the period including body length, chest circumference, abdomen circumference, and pelvic width was not affected by the bedding and no significant difference was seen in them, which is consistent with the results of Sutherland et al (2017). Sutherland et al (2017) showed that cement, gravel, chaff, and debris beddings cannot make a significant difference in calf growth performance. In this experiment, only the height from withers showed a significant difference.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, skeletal growth at the end of the period including body length, chest circumference, abdomen circumference, and pelvic width was not affected by the bedding and no significant difference was seen in them, which is consistent with the results of Sutherland et al (2017). Sutherland et al (2017) showed that cement, gravel, chaff, and debris beddings cannot make a significant difference in calf growth performance. In this experiment, only the height from withers showed a significant difference.…”
Section: Discussionsupporting
confidence: 90%
“…The difference between the two studies may be due to the fact that the calves in this study were older and, thus, were able to withstand cooler temperatures ( Gonzalez-Jimenez and Blaxter, 1962 ; Webster et al, 1978 ). However, a number of studies have documented that skin temperature is not directly related to either rectal or vaginal temperature ( Sutherland et al, 2017 ; Scoley et al, 2019 ). Therefore, although calf jackets appear to create a warmer microenvironment for the calf, they may not be having any impact on core body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Panivivat et al (2004) used a scoring system where tail head region, thighs, and legs were counted when soiled with manure. This scoring has been applied by Sutherland et al (2013Sutherland et al ( , 2014Sutherland et al ( , 2017 and Graham et al (2018). Other studies assessed different body regions and their degree of dirtiness (score or percentage): Terosky et al (1997) and Klein-Jöbstl et al (2014) focused on legs, thighs, and the belly, whereas Webster et al (1985) also included the back and the head.…”
Section: Short Communicationmentioning
confidence: 99%